Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m113.507392
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Reb1p Regulates DGK1-encoded Diacylglycerol Kinase and Lipid Metabolism in Saccharomyces cerevisiae

Abstract: Background: Diacylglycerol kinase produces phosphatidate, a major precursor for the synthesis of membrane phospholipids.Results: The expression of diacylglycerol kinase is induced by the Reb1p transcription factor, and the resulting activity increase is essential for the enzyme function in phospholipid synthesis.Conclusion: The Reb1p-mediated transcriptional activation regulates the expression of diacylglycerol kinase activity.Significance: Diacylglycerol kinase is regulated at the level of transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 101 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…This enzyme does not exhibit sequence similarity to DAG kinases from other species ( Han et al, 2008b ), and contains a short motif identified in a family of CTP-dependent phytol and dolichol kinases ( Shridas and Waechter, 2006 ). Together with PA phosphatase, this enzyme controls the levels of PA and DAG for phospholipid synthesis, membrane growth, and lipid droplet formation ( Qiu et al, 2013 ). The fact that the yeast DGK enzyme utilizes CTP, instead of ATP, as the phosphate donor in the reaction, explains why an ATP-dependent DAG kinase activity or a putative gene encoding a DAG kinase enzyme had not been identified in S. cerevisiae before ( Han et al, 2008a ).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme does not exhibit sequence similarity to DAG kinases from other species ( Han et al, 2008b ), and contains a short motif identified in a family of CTP-dependent phytol and dolichol kinases ( Shridas and Waechter, 2006 ). Together with PA phosphatase, this enzyme controls the levels of PA and DAG for phospholipid synthesis, membrane growth, and lipid droplet formation ( Qiu et al, 2013 ). The fact that the yeast DGK enzyme utilizes CTP, instead of ATP, as the phosphate donor in the reaction, explains why an ATP-dependent DAG kinase activity or a putative gene encoding a DAG kinase enzyme had not been identified in S. cerevisiae before ( Han et al, 2008a ).…”
Section: Discussionmentioning
confidence: 99%
“…The level of PA can be enhanced by overexpression of Dgk1p, which leads to nuclear/ER membrane localization of the repressor Opi1p and to derepression of UAS INO controlled gene expression thus increasing PL synthesis (Han et al, 2008b;Fakas et al, 2011). Dgk1p expression itself is regulated by the essential transcription factor Reb1p which also activates the expression of other lipid metabolic genes (Qiu et al, 2013). Besides this enzymatic regulation, the presence of inositol or zinc in the growth medium as well as the growth phase affect the gene expression under the control of UAS INO .…”
Section: Phospholipidsmentioning
confidence: 99%
“…The sequence of S. cerevisiae DGK1p is unlike that of DGKs from other species and contains a CTP transferase domain essential for the protein's DGK activity [40]. The combination of DGK1p and phosphatidate phosphatase encoded by PAH1 can regulate the levels of DAG and PA for phospholipid synthesis [41].…”
Section: Discussionmentioning
confidence: 99%